Real‐world treatment patterns and clinical outcomes of Japanese patients with non‐muscle invasive bladder cancer receiving intravesical bacillus Calmette–Guérin treatment. (21st May 2022) - Miyake, Makito; Kikuchi, Eiji; Shinozaki, Kenta; Piao, Yi; Hayashi, Nobuya; Koto, Ryo; Jinushi, Masahisa; Kobayashi, Takashi
Abstract : Objectives: To investigate current patterns and outcomes of intravesical bacillus Calmette–Guérin treatment in Japanese patients with bladder cancer, including the proportion of patients completing induction therapy, and time to subsequent treatments. Methods: This retrospective cohort study utilized administrative claims data from the Medical Data Vision Co., Ltd. database to identify patients with a diagnosis of bladder cancer who had received ≥1 prescription of intravesical bacillus Calmette–Guérin between April 2008 and September 2015, and had ≥1 database record dated ≥12 weeks after the initial bacillus Calmette–Guérin dose. Patients were followed until September 2018, the last date of available data, or in‐hospital death. Patients receiving six doses of bacillus Calmette–Guérin at intervals of <21 days were considered to have completed induction according to guidelines. Time from initial bacillus Calmette–Guérin dose to subsequent bladder cancer treatment after the end of treatment was defined as the recurrence‐free duration. Results: Of 6140 patients identified (median age 73.0 years; 83.4% males), 4588 (74.7%) completed induction and 1552 (25.3%) did not. Median recurrence‐free duration was 64.4, 77.7, and 31.6 months in the overall, complete‐induction and incomplete‐induction cohorts, respectively. Corresponding 3‐year recurrence‐free rate was 56.3%, 59.0%, and 48.2% in these groups. The rate of cystectomy was approximately 6% at 5 years in all cohorts. Conclusions: Approximately 75% of Japanese patients who undergo intravesical bacillus Calmette–Guérin treatment receive a guideline‐compliant induction regimen, but outcomes were not satisfactory, highlighting the need for more effective treatments for non‐muscle invasive bladder cancer.